(untitled) (Global Journal of Medical Research, 2014)
Drugs are eliminated from the body either unchanged as the parent drug or as metabolites. Nimesulide drug belongs to a wide class of medicines called antiinflammatory nonsteroidal drugs (NSAID). NSAIDs are well known for their antipyretic, anti-inflammatory, and analgesic properties. Renal clearance of nimesulide correlated with creatinine clearance. The present research work was planed to determine urinary excretion and renal clearance of nimesulide after its oral administration. Blood and urine samples of the human male volunteers (n=10), after the oral administration of drug, were collected at predetermined time intervals. The concentration of the nimesulide in urine and plasma of male volunteers was determined by HPLC. Statistical analysis was performed in order to determine the significance of the results.